Dermatoses na síndrome de down - Beatriz Elizabeth Bagatin Veleda Bermudez; Charles da Silva Gomes; Iolanda Maria Novadzki; Susana Girald (Residência Pediátrica)
Down syndrome is the most common chromosomal disorder, affecting 1 in 700 live births. It has typical physical features and multisystem anomalies that include the skin. This study aims determine the dermatological characteristics among patients attended at a Down syndrome outpatient clinic. Cross-sectional study conducted by the review of medical records of patients attended in 2018. Data were submitted to descriptive analysis using Statistica® software. Dermatologists worked at the Down syndrome outpatient clinic one day per week. They evaluated 838 patients, of which 474 (56.6%) were male and 364 (43.4%) were female. The most frequent dermatoses were xerosis (57.6%), follicular keratosis (26.3%), papular urticaria (17.6%), palmoplantar hyperkeratosis (11.9%) and sudammine (9.1%). Diagnosing and treating dermatoses in Down syndrome patients are an integral part of the clinical follow-up of this population, and skin self-care should be encouraged from childhood.